Gap between Educational Research and Praxis in Biological Education - Tamara Esquivel-Martín; Beatriz Bravo-Torija; José Manuel Pérez Martín (Universidad Autónoma de Madrid, 2019)
Cell division is the conceptual basis to understand processes such as tissue growth or regeneration, as well as inherited diseases, reproductive problems or cancer, which are of great interest to the population nowadays. A correct scientific literacy in this sense needs a teaching-learning process that considers the purposes of scientific-technological development and its consequences in society and the environment. It analyses several publications about cell division between 2000-2017. And it examines how Secondary Education teachers make use of these investigations in their daily practice. To do so, a documentary research was carried out in 14 Didactic of Experimental Sciences journals and a questionnaire with 9 questions was designed, getting 117 answers. The results show that teachers do not usually read scientific journals publications, and that, if needed, the most interesting topics are those that propose classroom activities and educational resources which are not the publications of greater impact. It is shown a weak transfer from educational research in Didactic of Experimental Sciences to teaching practice in Biology classrooms of Secondary Education. Possible causes and implications of such a significant problem in Education are discussed in the article.